Rancang Bangun Pembangkit Listrik Picohidro Curah Hujan - Pijar Nurofiq Pratama; Indra Riyanto; Suwasti Broto (MAESTRO, 2023)
Indonesia has a fairly high rainfall of (2000-3000 mm per year) This has the potential to be used as an alternative energy source for power generation. In this final project, a picohydro power generation system was designed with energy sources derived from rainfall. The designed system consists of gutters with a height of 1 m, 1/2" pipe, YF-S201 water flow, Picohidro Generator, INA219 sensor, Arduino Mega 2560, RTC DS3231, LCD, I2C, Micro SD Card, and 5 watt dc lamp load. The way the system works is that when it rains, the water will be collected by gutters which then the water will flow through pipes connected to the water flow and generator. Water that passes through the water flow and generator will rotate the turbine so that it produces data on water discharge and electrical power. The INA219 sensor will read the current and voltage as well as the power generated from the generator with a 5 watt dc lamp load. Water discharge and power data will then be displayed on the LCD and stored on the SD Card. The designed system is tested by means of three test scenarios namely testing 1 single generator, 2 series connection generators, and 2 parallel connection generators. From the results of system testing, the highest data was obtained in testing 1 generator that produced 25.64 mW of power with a potential energy of 1.5384 Joules.